High-performance enhancement-mode AlGaN/GaN MOS-HEMTs with fluorinated stack gate dielectrics and thin barrier layer - 高涛 徐锐敏 张凯 孔月婵 周建军 孔岑 郁鑫鑫 董迅 陈堂胜 (Journal of semiconductors, 2016)
We present high-performance enhancement-mode AlGaN/GaN metal-oxide-semiconductor highelectron mobility transistors（MOS-HEMTs） by a fluorinated gate dielectric technique.A nanolaminate of an Al_2O_3/La_xAl_（1-x）O_3/Al_2O_3 stack（x≈0.33） grown by atomic layer deposition is employed to avoid fluorine ions implantation into the scaled barrier layer.Fabricated enhancement-mode MOS-HEMTs exhibit an excellent performance as compared to those with the conventional dielectric-last technique,delivering a large maximum drain current of 916 mA/mm and simultaneously a high peak transconductance of 342 mS/mm.The balanced DC characteristics indicate that advanced gate stack dielectrics combined with buffered fluorine ions implantation have a great potential for high speed GaN E/D-mode integrated circuit applications.